Assessing the impact of COVID-19 on rural women and men in Dang District, Nepal - Alvi, Muzna; Gupta, Shweta; Barooah, Prapti (International Food Policy Research Institute, 2022)
To understand the impact of COVID-19 on rural women, we designed a longitudinal panel study with five rounds of phone survey data collection in Dang district in the mid-western region of Nepal. This note summarizes results from all rounds. The study sample was drawn using systematic random sampling from a large, representative household listing survey conducted in February 2020 across four rural municipalities in Dang district. Figure 1 provides a detailed description on the study timeline and sample size covered in each round.